2008
DOI: 10.1088/0022-3727/41/10/105105
|View full text |Cite
|
Sign up to set email alerts
|

Swift heavy ion irradiation-induced defects and electrical characteristics of Au/n-Si Schottky structure

Abstract: The formation and evolution of defects induced by 100 MeV Si7+ ion irradiation in the Au/n-Si (1 0 0) Schottky barrier structure were studied and correlated with the electrical characteristics of the structure. The Schottky barrier decreases to 0.67 ± 0.01 eV after irradiation at a fluence of 1 × 1011 ions cm−2 and remains immune to further irradiation up to a fluence of 1 × 1012 ions cm−2. A combination of in situ deep level transient spectroscopy and current–voltage measurements of Au/n-Si diodes demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
(20 reference statements)
1
2
0
Order By: Relevance
“…Afterward, the I R decreases as the ion fluence increases and a value of 3.8 × 10 −5 A is measured after irradiation with 1 × 10 13 ions cm −2 , which is about one-fourth of the value of without irradiation. These results are new compared to reported irradiation studies in silicon devices where irradiation results in a decreased value of ϕ B and increased I R up to a critical ion fluence and at the higher irradiation fluences, these parameters saturated [11,16,20,24]. These results indicate that the Schottky barrier characteristics at the Pd/n-Si interface is improved after irradiation at higher fluence.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Afterward, the I R decreases as the ion fluence increases and a value of 3.8 × 10 −5 A is measured after irradiation with 1 × 10 13 ions cm −2 , which is about one-fourth of the value of without irradiation. These results are new compared to reported irradiation studies in silicon devices where irradiation results in a decreased value of ϕ B and increased I R up to a critical ion fluence and at the higher irradiation fluences, these parameters saturated [11,16,20,24]. These results indicate that the Schottky barrier characteristics at the Pd/n-Si interface is improved after irradiation at higher fluence.…”
Section: Resultssupporting
confidence: 57%
“…This exposure to radiation and energetic ions can modify the MS interface, which will lead to the modified barrier parameters and the transport properties 3 Author to whom any correspondence should be addressed. [11][12][13]. Therefore, irradiation studies with energetic ions are extremely helpful to simulate the device's performance in a radiation ambiance.…”
Section: Introductionmentioning
confidence: 99%
“…They also performed irradiation on same diode by using 100 MeV Si 7+ ion and observed that the Schottky barrier decreases after irradiation at a fluence of 1 × 10 11 ions cm −2 and remains immune to further irradiation up to a fluence of 1 × 10 12 ions cm −2 . A combination of insitu deep level transient spectroscopy and I-V measurements of Au/n-Si diodes demonstrates that 100 MeV silicon ion irradiation introduces a hydrogen related defect complex, which has a major influence on the SBH and the leakage current in the irradiated structure [547]. The group has also carried out the in-situ I-V and C -V characterization.…”
Section: Au/si and Ag/simentioning
confidence: 99%